Monitoramento ambiental e higiene ocupacional em uma indústria química da cidade de São Carlos SP: ênfase em qualidade do ar interior - Kawamoto, Mayumi Silva (2011)
In a workplace, workers are daily exposed to various physical and chemical agents which become health hazards and jeopardize the welfare of the affected individuals. Considering the issue of occupational hygiene and environmental monitoring, this study aimed to evaluate the indoor air quality in the production environment of an industry of paints, varnishes, solvents and products for leather in the city of São Carlos. Were monitored from August 2010 to March 2011, in about four hours by sampling, the following parameters: total particulate matter and respirable fractions, levels of carbon dioxide, noise, temperature and humidity, and also proceeded to the chemical characterization of particulate material collected by the technique of X-Ray Fluorescence and the evaluation of total volatile organic compounds (VOC s). The results showed values above the temperature recommended by the RE/ANVISA nº 9 with an average of 27ºC for the period tracked and humidity values with an average of 52%, which is considered within the recommended by the same standard. The noise levels, in 14 of the 31 samples, were above permitted by NR 15 which is 90 dB (A) for 4 hours with an average value of 73,13 dB(A) for the months sampled and peaks above 90 dB(A) in almost all months. The levels of CO2 are within permitted by NR 15 (3900 ppm) and RE/ANVISA nº 9 (1000 ppm). As for particulate matter, the MP2,5 fraction had average value below 7 μg/m³ and is within the recommended values, as the MP10 and MPT are outside the recommended by OMS and RE/ANVISA nº 9, considering that the MPT is above the recommended 13 days of sampling, ranging from 34,6 to 182,6 μg/m³ in the months sampled. Chemical analysis quantified the elements: Al, Ca, Cr, Cu, Fe, K, Mn, P, Pb, S, Si, Sr, Ti, Zn, and the elements of higher concentration in the sampled period were: Al, Fe and Si with maximum concentration of 47,68 μg/m³, 32,81 μg/m³ and 45,25 μg/m³, respectively. The average value for VOC s was 17,85 ppm.